Co-expression of P173S Mutant Rice EPSPS and igrA Genes Results in Higher Glyphosate Tolerance in Transgenic Rice - Fartyal, Dhirendra; Agarwal, Aakrati; James, Donald; Borphukan, Bhabesh; Ram, Babu; Sheri, Vijay; Yadav, Renu; Manna, Mrinalini; Varakumar, Panditi; Achary, V. Mohan M.; Reddy, Malireddy K. (Frontiers in Plant Science, 2018)
Weeds and their devastating effects have been a great threat since the start of agriculture. They compete with crop plants in the field and negatively influence the crop yield quality and quantity along with survival of the plants. Glyphosate is an important broad-spectrum systemic herbicide which has been widely used to combat various weed problems since last two decades. It is very effective even at low concentrations, and possesses low environmental toxicity and soil residual activity. However, the residual concentration of glyphosate inside the plant has been of major concern as it severely affects the important metabolic pathways, and results in poor plant growth and grain yield. In this study, we compared the glyphosate tolerance efficiency of two different transgenic groups over expressing proline/173/serine (P173S) rice EPSPS glyphosate tolerant mutant gene (OsmEPSPS) alone and in combination with the glyphosate detoxifying encoding igrA gene, recently characterized from Pseudomonas. The molecular analysis of all transgenic plant lines showed a stable integration of transgenes and their active expression in foliar tissues. The physiological analysis of glyphosate treated transgenic lines at seed germination and vegetative stages showed a significant difference in glyphosate tolerance between the two transgenic groups. The transgenic plants with OsmEPSPS and igrA genes, representing dual glyphosate tolerance mechanisms, showed an improved root-shoot growth, physiology, overall phenotype and higher level of glyphosate tolerance compared to the OsmEPSPS transgenic plants. This study highlights the advantage of igrA led detoxification mechanism as a crucial component of glyphosate tolerance strategy in combination with glyphosate tolerant OsmEPSPS gene, which offered a better option to tackle in vivo glyphosate accumulation and imparted more robust glyphosate tolerance in rice transgenic plants.